The narrative review of recent studies in understanding the relationship between gut (microbiota)-brain axis, nutrition and cognitive function - Taufiq Fredrik Pasiak; Tjhin Wiguna; Rini Sekartini; Juwalita Surapsari; Tonny Sundjaya; Erika Wasito; Ray Wagiu Basrowi; Melissa Stephanie Kartjito (Indonesian Nutrition Association, 2023)
The concept of the gut (microbiota)-brain axis, which influences the development and function of the gastrointestinal, immune, neuroendocrine, and metabolic systems, is gaining popularity. Recent animal studies have demonstrated that the gut (microbiota)-brain axis also plays a role in establishing cognitive function. It is known that a disruption in the environment's microbiota balance can increase disease susceptibility in children. Historically, it has been hypothesized that neurodevelopmental disorders are the results of a disruption in children’s health. However, it is becoming clear that the gut microbiota and the central nervous system communicate in both directions, which could explain how microbiota affects cognitive function. Dietary factors also play important role in the central nervous system via the gut (microbiota)-brain axis, demonstrating the importance of nutrition in optimizing cognitive function. This narrative review of recently published studies and current knowledge aims to elucidate the relationship between the gut (microbiota)-brain axis and cognitive function, as well as the variables that may influence it.